2007
DOI: 10.1007/s00404-007-0407-4
|View full text |Cite
|
Sign up to set email alerts
|

Congenital diaphragmatic hernia, etiology and management, a 10-year analysis of a single center

Abstract: The overall survival in CDH is around 50%, antenatal endoscopical therapy may only be considered, if the diagnosis is performed in the early second trimester, and selection criteria such as the lung to head ratio, associated defects and the chromosomal status can be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
10
0
3
Order By: Relevance
“…Complete or mosaic chromosome aneuploidies, large chromosome deletions/duplications, and complex chromosome rearrangements identifiable by karyotype are present in 10–35% of CDH cases and occur at greatest frequency in non-isolated, prenatally diagnosed cases [2,611]. An additional 3.5–13% of cases without identifiable karyotype abnormalities have copy number variants (CNVs) including microdeletions or microduplications identifiable by chromosome microarray analysis, which offers higher resolution over a standard karyotype [1220].…”
Section: Geneticsmentioning
confidence: 99%
“…Complete or mosaic chromosome aneuploidies, large chromosome deletions/duplications, and complex chromosome rearrangements identifiable by karyotype are present in 10–35% of CDH cases and occur at greatest frequency in non-isolated, prenatally diagnosed cases [2,611]. An additional 3.5–13% of cases without identifiable karyotype abnormalities have copy number variants (CNVs) including microdeletions or microduplications identifiable by chromosome microarray analysis, which offers higher resolution over a standard karyotype [1220].…”
Section: Geneticsmentioning
confidence: 99%
“…Congenital diaphragmatic hernia (CDH) can be diagnosed accurately by second‐trimester ultrasound examination1. Despite all efforts, morbidity and mortality in cases diagnosed prenatally remain high and are thought to be related to the severity of pulmonary hypoplasia and pulmonary arterial hypertension (PAH)2. Many studies have shown that a complicated neonatal course and/or mortality are related to decreased fetal lung size observed on ultrasound or magnetic resonance imaging, the presence of herniated liver and decreased pulmonary vascularity3–12.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is in contrast to other studies where TOP rates ranged from 21% to 44%. (1,5,7,22,24) As there is no general consensus on the counselling and management of CDH, there can be many reasons for this discrepancy, which are not within the scope of this paper.…”
Section: Discussionmentioning
confidence: 96%